Spirituality, dual career family worker, demographic factors, and organizational commitment: evidence from religious affairs in Indonesia - Abdul Aziz Nugraha Pratama; Hikmah Endraswati (IAIN Salatiga, 2017)
The purpose of this study is to specify whether spirituality, age, and tenurehave an effect on organizational commitment and to determine whether themoderating variables, i.e. dual career family worker, moderates the effect ofspirituality, age, and tenure on organizational commitment. The samples ofthe study were 90 staffs and lecturers of three educational institutions under the Ministry of Religious Affairs located in Central Java. They were IAINSurakarta, IAIN Salatiga, and MTsN 1 Surakarta. The research used Moderated Regression Analysis to analyze the data. The results showed that spirituality and tenure positively affect organizational commitment and dual careerfamily worker moderated the effect of spirituality and tenure on organizational commitment. Dual career family worker in this study can be categorized as a quasi-moderation variable.Tujuan dari penelitian ini adalah untuk mengetahui apakah spiritualitas, usia,dan masa jabatan berpengaruh terhadap komitmen organisasi dan untukmenentukan apakah dual career family worker sebagai variabel moderasi dapatmemoderasi pengaruh spiritualitas, usia, dan masa jabatan terhadap komitmenorganisasi. Penelitian ini menggunakan 90 karyawan dan dosen sebagai sampeldari tiga institusi pendidikan di bawah Kementerian Agama di Jawa Tengah:IAIN Surakarta, IAIN Salatiga, dan MTsN 1 Surakarta. Teknik analisis yangdigunakan dalam penelitian ini adalah Analisis Regresi Moderasi. Hasilnyamenunjukkan bahwa spiritualitas dan masa jabatan secara positif mempengaruhikomitmen organisasi dan dual career family worker sebagai variabel moderasimampu memoderasi spiritualitas dan masa jabatan terhadap komitmenorganisasi. Dual career family worker dalam penelitian ini dimasukkan sebagaivariabel moderasi kuasi.